Working Conditions and Environment in Health - Neffa, Julio César (2015)
For decades now and under the impetus of the ILO, the work process began to be directly related to the workers' health. It revealed that those who work - any status in the company or organization - involve their bodies when placing in a job, and have to adopt productive postures and gestures that generate fatigue. On the other hand, they must get involved using mental and psychological dimensions (affective and relational aspects) due to when facing the company demands, they must make a creative effort to compensate the problems arising in the description of their tasks, if incidents happen, malfunctions appear, or involuntary interruptions take place, requiring them to make an effort to develop the activity and achieve the purposes. The researches of ergonomists, sociologists and labor economists, as well as those who study the psychodynamic of work, have highlighted the psychosocial risks at work. This new perspective is a challenge for guidance professionals, since in the past these issues were ignored.